Cypermethrin resistance in Rhipicephalus microplus from cattle farms in the Ecuadorian Amazon - JOSÉ ZAPATA; LEONARDO CABEZAS; MARITZA VACA; JULIO LLERENA; DIEGO MASAQUIZA (Asian Journal of Agriculture, 2026)
Abstract. Zapata J, Cabezas L, Vaca M, Llerena J, Masaquiza D. 2026. Cypermethrin resistance in Rhipicephalus microplus from cattle farms in the Ecuadorian Amazon. Asian J Agric 10 (1): g100180. https://doi.org/10.13057/asianjagric/g100180. Acaricide resistance in the cattle tick Rhipicephalus microplus represents an important sanitary challenge associated with herd management practices in tropical livestock systems. In the Ecuadorian Amazon, control of R. microplus frequently relies on the non-standardized use of chemical acaricides, with cypermethrin widely applied and often used with limited product rotation and technical guidance. The continued use of the same active ingredient contributes to the resistance of ticks to this product. In this study, the in vitro sensitivity of R. microplus to cypermethrin was evaluated using the Larval Packet Test (LPT) at four livestock farms in La Joya de los Sachas, and the relationship with management practices was determined. One hundred adult female ticks were collected and incubated under laboratory conditions to obtain larvae for the bioassays, which were exposed to different concentrations of cypermethrin; lethal concentrations were determined using Probit models. Additionally, a survey was administered to producers regarding the use of acaricides, treatment frequency, treatment rotation, herd size, and access to veterinary assistance. With regard to mortality, a dose-response pattern was observed across the different concentrations evaluated. LC50 values ranging from 0.009 to 0.037 mg/mL were found, indicating variability in susceptibility to cypermethrin across different farms. When classified based on the thresholds, one population was susceptible (RR50=1.00), and the others were classified as tolerant (RR50=3.11-4.11). Farms reporting acaricide rotation, lower treatment frequency, and technical assistance tended to exhibit lower RR50 values, while larger herd sizes and more frequent treatments were associated with higher resistance ratios. These findings suggest that integrated approaches combining resistance monitoring with improved management practices may contribute to sustaining tick control in cattle production systems of the Ecuadorian Amazon.